Beyond GDP: using healthy lifetime income to trace well-being over time with estimates for 193 countries - Zhang, Junlai; Prettner, Klaus; Chen, Simiao; Bloom, David E. (Social science & medicine, 2023)
We measure well-being across 193 countries from 1990 to 2019 using a new indicator: healthy lifetime income (HLI). Apart from the income component as captured by standard per capita gross domestic product, HLI incorporates health as a second important component. Overall, HLI can be interpreted as the income of the average person in an economy during the years in which the person is in good health. We show that HLI has particular strengths as compared with other measures such as the Human Development Index. These include requiring only easily accessible data for its construction, having an immediate economic interpretation and unit of measurement, not needing the application of arbitrary weights of subcomponents, and not being bounded from above. As compared with using per capita gross domestic product as a metric for well-being, we find that countries with better population health tend to fare better in the rankings. This provides a rationale for investments in health and helps shift the focus from material well-being (as an instrumental indicator of well-being) toward health (as an intrinsic goal).
Online veröffentlicht am 13. Januar 2023, Artikelversion vom 19. Januar 2023
Gesehen am 22.11.2023